(untitled) (Research, Society and Development, 2022)
Coagulase-negative staphylococci (CoNS) have been associated with a range of human health issues such as medical device-related infection, localized skin infection, or direct infection, are recognized as comprising the main part of human normal microbiota and associated with severe and intensive infections, causing infections in humans, especially immunocompromised patients and neonates. S. haemolyticus is, after Staphylococcus epidermidis, the second most frequently isolated CoNS from clinical cases, notably from blood infections, including sepsis. The most important factor might be the ability to acquire multiresistance against available antimicrobial agents, even glycopeptides. It is widespread in hospitals and among medical staff, resulting in being an emerging microbe causing nosocomial infections. This review discuss aspects of S. haemolyticus bloodstream infections associated, virulence factors, and the ability of biofilm formation on medical devices surfaces. The great adaptability and the ability to survive in the hospital environment, especially on medical devices, S. haemolyticus becomes a crucial factor in nosocomial infections caused by multiresistant strains.